The effectiveness of problem-based learning with environmental-based comic in enhancing students environmental literacy - Muhammad Wajdi; Asham Bin Jamaluddin; Nurdiyanti Nurdiyanti; Nurul Maghfirah (International Journal of Evaluation and Research in Education (IJERE), 2022)
Environmental literacy is an attitude and behavior that must be possessed by a student in protecting the environment. Therefore, it is necessary to carry out a plan and action to empower environmental literacy through education. This study aimed to determine the effect of the problem-based learning with environmental-based comic (PBLEC) model in empowering students' environmental literacy in Indonesia. This type of research was a quasi-experimental posttest-pretest non-equivalent control group design study involving 97 students at the University of Muhammadiyah Makassar, South Sulawesi, Indonesia. Students' environmental literacy data was obtained by using an exam technique using an essay test instrument sheet, then the results were analyzed using descriptive statistics and one-way inferential analysis of covariance (ANCOVA). The results of statistical analysis showed that the PBLEC model has an effect on students' environmental literacy. The average score achieved by students in the class group using PBLEC is higher than students who are taught by the problem-based learning (PBL) learning process and conventional learning. Therefore, the use of the PBLEC model can be used in the learning process as an effort to grow and improve student environmental literacy.